Acute ischemic stroke management: concepts and controversies.A narrative review. (2nd January 2021) - Li, Ka Hou Christien; Jesuthasan, Aaron; Kui, Christopher; Davies, Ruth; Tse, Gary; Lip, Gregory Y. H.
ABSTRACT: Introduction: Amongst the 25.7 million survivors and 6.5 million deaths from stroke between 1990 and 2013, ischemic strokes accounted for approximately 70% and 50% of the cases, respectively. With patients still suffering from complications and stroke recurrence, more questions have been raised as to how we can better improve patient management. Areas covered: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement and Newcastle-Ottawa Scale (NOS) were adopted to ensure a comprehensive inclusion of quality literature from various sources. PubMed and Embase were searched for evidence on thrombolysis, mechanical thrombectomy, artificial intelligence (AI), antiplatelet therapy, anticoagulation and hypertension management. Expert opinion: The directions of future research in these areas are dependent on the current level of validation. Endovascular therapy and applications of AI are relatively new compared to the other areas discussed in this review. As such, future studies need to focus on validating their efficacy. As for thrombolysis, antiplatelet and anticoagulation therapy, their efficacy has been well-established and future research efforts should be directed toward adjusting its use according to patient-specific factors, starting with factors with the most clinical relevance and prevalence.